Prevalence of Staphylococcus aureus in Intensive care Units and Post Operative Ward as a possible source of Nosocomial infection: An experience of tertiary care hospital - Bhattarai, P; Dhungel, BA; Shah, P; Amatya, J (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Hospital Acquired Infection (HAI) also called nosocomial infection is a global problem. It also acts as a leading cause of death and increased morbidity among hospitalized patients. Staphylococcus aureus is one of the commonest pathogens causing HAI and is also closely associated with human body. WHO study has shown highest prevalence of HAI in Intensive care unit (ICU), Neonatal care unit (NICU), Post operative ward (POW). Hence it becomes very imperative to check the prevalence of HAI. Therefore this study was carried out to determine the prevalence of S. aureus in hospital environment as a possible source for HAI. Material and Methods: Environmental samples and blood samples of the patients were collected from ICU, NICU, POW using sterile cotton swabs during study period. Standard protocol was followed to isolate and identify S. aurues which was followed by antibiotic sensitivity tests. Results: A total of 216 environmental samples were collected out of which 18.98% (41) samples showed the presence of S. aureus. It was also isolated from the blood samples of patients admitted to ICU (7.5%) and NICU (6.8%). None of the isolates from environmental samples were MRSA(methycillin resistant Staphylococcus aures). Conclusion: S. aureus was found as a prominent environmental flora of hospital setting. Presence of these organisms in sensitive units like ICU, NICU, POW and the isolation of S. aureus from clinical samples indicates a possibility of HAI. It indicates the necessity of continuous surveillance of hospital environmental for quality control. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7882 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):21-25